Deconstruction of Roman law and construction of positive law - Cvetković-Đorđević Valentina V. (Zbornik Radova: Pravni Fakultet u Novom Sadu)
The interpretation of Roman legal sources directly affects the creation of a positive legal order. In history, two basic interpretations of Roman law have been distinguished so far, which were translated into two codes: the French Civil Code from 1804 and the German Civil Code from 1900. The two codes determine the nature of the collective in a fundamentally different way and regulate its actions in legal transactions. According to the German Civil Code, the collective has an abstract nature, which is why it gets the status of a legal entity that does not have its own will but participates in legal transactions through representatives. An alternative solution to the concept of the collective and its actions is present in the French Civil Code, which is based on the original Roman understanding that the collective (the people) has a concrete nature and that it is made up of concrete individuals who participate in the formation of the collective's unique will. Two different conceptions of the collective and its action reflected the understanding of individual legal action when work is undertaken through another.